2019
DOI: 10.3390/ani9121147
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Genetic Parameters for Semen Traits in Spanish Dairy Sheep

Abstract: Simple Summary:The limited studies addressing the estimation of genetic parameters for ram semen traits in different breeds show a wide variation, highlighting the importance of studying these traits for individual breeds. Therefore, this work aimed to estimate genetic parameters for traits related to semen production and quality in five dairy sheep breeds. For that, ejaculates of rams from Assaf, Churra, Latxa Cara Negra, Latxa Cara Rubia, and Manchega breeds were analyzed. Estimates of the genetic covariance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 18 publications
5
14
1
Order By: Relevance
“…On the other hand, for ratio-defined traits such as PROP and MWB, theoretical investigations and computer simulations have been conducted ( Iwaisaki and Wilton, 1993 ; Ogawa and Satoh, 2020 ; Yazaki et al, 2021 ), and the results should be interpreted with caution. The results of genetic parameter estimation for semen production traits may contain bias due to both selection at a young age and data editing ( Tusell et al, 2012 ; Atagi et al, 2017 ; Pelayo et al, 2019 ; Olsen et al, 2021 ). Furthermore, genetic correlations of semen production traits may differ among breeds ( Wolf, 2010 ; Li et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, for ratio-defined traits such as PROP and MWB, theoretical investigations and computer simulations have been conducted ( Iwaisaki and Wilton, 1993 ; Ogawa and Satoh, 2020 ; Yazaki et al, 2021 ), and the results should be interpreted with caution. The results of genetic parameter estimation for semen production traits may contain bias due to both selection at a young age and data editing ( Tusell et al, 2012 ; Atagi et al, 2017 ; Pelayo et al, 2019 ; Olsen et al, 2021 ). Furthermore, genetic correlations of semen production traits may differ among breeds ( Wolf, 2010 ; Li et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The phenotypic data used in this study involved 2,020 ewes belonging to the Assaf (n = 1,039; number of flocks = 4) and Churra breeds (n = 981; number of flocks = 2). These samples were previously analyzed by Sánchez-Mayor et al (2019) for the Assaf breed and Pelayo et al (2019) for the Churra breed. After consultation with the Research Ethics Committee of the University of León, as the animals have been sampled within the routine practices carried out on commercial farms, formal ethical approval was deemed not necessary.…”
Section: Animals and Phenotypesmentioning
confidence: 99%
“…The few studies that do exist indicate that heritability of semen traits is generally low to moderate. For example, a study on Spanish dairy rams estimated the heritability for common ejaculate quality traits including volume, concentration and motility to range from 0.077 to 0.304 using a dataset consisting of ejaculates from 3289 rams across five breeds [ 18 ]. Similarly, a study focused on 9- and 12-month old Ethiopian rams estimated the heritability for ejaculate volume to be 0.07 and 0.11, for gross motility to be 0.32 and 0.27, for individual motility to be 0.32 and 0.16, and for concentration to be NA and 0.17 respectively [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in livestock species have also estimated the genetic correlation between different combinations of semen traits [ 10 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Specifically, in sheep, previous studies vary considerably in terms of the reported estimates for genetic correlations between different traits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation